ЭФФЕКТИВНОСТЬ ИСПОЛЬЗОВАНИЯ ИНТЕРАКТИВНЫХ МЕТОДОВ В ПРОЦЕССЕ ВУЗОВСКОГО ОБУЧЕНИЯ РУССКОМУ ЯЗЫКУ (Интерактивные методы обучения на уроках русского языка) - Убайдова, Д.А. (SCIENCE and SOCIETY, 2022)
The use of this topic is due to the fact that today there is a need to improve the teaching of the Russian language. This increased the vital need for the search for advanced experience of new pedagogical technologies and their practical implementation after the experiment into the learning process. The logical conclusion is that the task of creating innovative scientific developments in education and implementation in pedagogical practice is even more actualized.